I didn't say that! Uses of SAY in mediation discourse. (December 2017) - Janier, Mathilde; Reed, Chris
While several taxonomies of meta-discourse exist, none clearly explains speakers' strategies in mediation. Mediators, however, seem to rely a lot on meta-discourse to manage the argument while preserving their neutrality. This article proposes corpus analyses to detect mediation participants' discourse strategies and highlight the role and function of a meta-discourse element – the verb 'to say'. This article is a first step towards the elaboration of a taxonomy for the analysis of argumentative meta-discourse and brings new insights into meta-discourse in argumentative dialogues and mediation discourse in general.